2017
DOI: 10.1111/jvh.12834
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of telbivudine in late pregnancy to prevent mother‐to‐child transmission of hepatitis B virus: A multicenter prospective cohort study

Abstract: Infection of hepatitis B virus (HBV) occurs in ~10% of infants of HBV-infected mothers with positive hepatitis B e antigen (HBeAg) after immunoprophylaxis. We aimed to evaluate the safety and efficacy of telbivudine used during late pregnancy for preventing mother-to-child transmission of HBV. We conducted a multicenter prospective cohort study in 5 hospitals from 2012 to 2014, which enrolled HBV-infected singleton pregnant women with positive HBeAg. By their choice, women were divided into therapy (telbivudin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
69
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 62 publications
(74 citation statements)
references
References 38 publications
3
69
2
Order By: Relevance
“…The incubation period of HBV infection is 30 to 180 days, which means that the current universal neonatal vaccination programs mainly target the peripartum transmission. Many studies as well as our results found that most neonates with HBsAg and/or HBV DNA positivity at birth became seronegative later after the standard infant immunoprophylaxis. The presence of HBsAg and/or HBV DNA at birth may be transient and does not indicate a definite infection; therefore, MTCT was proposed to be defined with infant seromarker measurement at some specific time points, usually at age 6 to 12 months after the HBV vaccination programs .…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…The incubation period of HBV infection is 30 to 180 days, which means that the current universal neonatal vaccination programs mainly target the peripartum transmission. Many studies as well as our results found that most neonates with HBsAg and/or HBV DNA positivity at birth became seronegative later after the standard infant immunoprophylaxis. The presence of HBsAg and/or HBV DNA at birth may be transient and does not indicate a definite infection; therefore, MTCT was proposed to be defined with infant seromarker measurement at some specific time points, usually at age 6 to 12 months after the HBV vaccination programs .…”
Section: Discussionsupporting
confidence: 79%
“…The target maternal HBV DNA level at delivery is theoretically as low as possible because of high correlation between MTCT rate and maternal viral loads. Practically, maternal HBV DNA less than 5.0 to 6.0 log 10 IU/mL is considered an anticipated level with minimal risk of MTCT at delivery and the same prior to amniocentesis because MTCT was absent when maternal HBV DNA was less than 7.0 log 10 IU/mL in previous and our studies. Therefore, it is feasible to give at least 4 weeks of antiviral treatment to highly viremic mothers and to achieve an aforementioned target HBV DNA level before amniocentesis.…”
Section: Discussionmentioning
confidence: 48%
See 2 more Smart Citations
“…Of the 32 RCTs that enrolled 4189 pregnant women, 17 studies evaluated the effect of LAM, 15 studies evaluated LdT, 3 studies evaluated TDF, and 3 studies evaluated both LAM and LdT . Of the 27 non‐RCT studies enrolling 5039 pregnant women, 10 evaluated LAM, 18 evaluated LdT, 3 studies evaluated TDF, 2 evaluated both LAM and LdT, and another 2 studies evaluated both LAM and TDF . The characteristics of pregnant women and newborns in the 59 studies are summarized in Table .…”
Section: Resultsmentioning
confidence: 99%